PENGARUH SUBSTITUSI TEPUNG TEMPE KEDELAI TERHADAP NILAI ORGANOLEPTIK DAN KANDUNGAN GIZI BISKUIT - Yuspitasari, Gian; Ansharullah, Ansharullah; Rejeki, Sri (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2023)
ABSTRACT This study aimed to determine the effect of tempeh flour substitution on the organoleptic and nutritional value of biscuits. This study used the CRD method (completely randomized design) which consisted of five treatments, namely T0 (100% flour), T1 (95% flour: 5% tempeh flour), T2 (90% flour: 10% tempeh flour), T3 (85% flour: 15% tempeh flour), and T4 (80% flour: 20% tempeh flour). Data were analyzed using analysis of variance and continued with Duncan's multiple range test (DMRT) at a 95% confidence level (α=0.05). The results show that the highest level of preference for hedonic scale panelists was found in the T1 treatment (95%: 5%) with average scores for color, aroma, taste, and texture reaching 4.03, 3.80, 3.78, and 3.58, respectively. The nutritional value analysis of the selected biscuits shows that they contained 7.61% water, 0.77% ash, 9.88% protein, 12.63% fat, and 69.11% carbohydrate. The water content of biscuit products did not meet the Indonesian national standard (SNI). Keywords: flour, tempeh flour, biscuits, nutritional value. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh substitusi tepung tempe kedelai terhadap nilai organoleptik dan gizi biskuit tempe. Penelitian ini menggunakan metodel RAL (Rancangan Acak lengkap) yang terdiri dari 5 perlakuan T0 (Tepung terigu 100%), T1 (Tepung terigu 95%: tepung tempe 5%), T2 (Tepung terigu 90%: tepung tempe 10%), T3 (Tepung terigu 85%: tepung tempe 15%),T4 (Tepung terigu 80% : tepung tempe 20%). Data dianalisis dengan menggunakan sidik ragam (analysis of varian) dan dilanjutkan dengan uji Duncan’s Multiple Range Test (DMRT) pada taraf kepercayaan 95% (α=0.05). Hasil penelitian menunjukkan tingkat kesukaan panelis skala hedonik tertinggi terdapat pada perlakuan T1 (95%: 5%) diperoleh nilai untuk warna (4,03), aroma (3,80), rasa (3,78), dan tekstur (3,58). Analisis nilai gizi biskuit terpilih menghasilkan kadar air sebesar 7,61 %, kadar abu 0,77 %, kadar protein 9,88 %, kadar lemak 12,63%, kadar karbohidrat 69,11 %. Namun komponen kadar air produk biskuit belum memenuhi standar nasional Indonesia (SNI). Kata kunci: tepung terigu, tepung tempe, biskuit, nilai gizi